2012
DOI: 10.1088/1748-9326/7/4/045905
|View full text |Cite
|
Sign up to set email alerts
|

Well-to-wheels energy use and greenhouse gas emissions of ethanol from corn, sugarcane and cellulosic biomass for US use

Abstract: Globally, bioethanol is the largest volume biofuel used in the transportation sector, with corn-based ethanol production occurring mostly in the US and sugarcane-based ethanol production occurring mostly in Brazil. Advances in technology and the resulting improved productivity in corn and sugarcane farming and ethanol conversion, together with biofuel policies, have contributed to the significant expansion of ethanol production in the past 20 years. These improvements have increased the energy and greenhouse g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
315
4
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(354 citation statements)
references
References 37 publications
12
315
4
4
Order By: Relevance
“…Among the GHGs, CO 2 and N 2 O are two primary components because of their large quantity and multiapproaches of production (Dunn et al 2013;Qin et al 2016). Theoretically, net CO 2 emissions resulting from the direct use of biofuels are far less than the utilization of fossil fuel, which has been proven by many studies (Dunn et al 2013;Wang et al 2012). By replacing fossil fuel, Liu et al (2017) quantified that the maximum potential switchgrass production on marginal land would reduce emissions by 29 million tons CO 2-eq /year.…”
Section: Ghg Emissionsmentioning
confidence: 99%
“…Among the GHGs, CO 2 and N 2 O are two primary components because of their large quantity and multiapproaches of production (Dunn et al 2013;Qin et al 2016). Theoretically, net CO 2 emissions resulting from the direct use of biofuels are far less than the utilization of fossil fuel, which has been proven by many studies (Dunn et al 2013;Wang et al 2012). By replacing fossil fuel, Liu et al (2017) quantified that the maximum potential switchgrass production on marginal land would reduce emissions by 29 million tons CO 2-eq /year.…”
Section: Ghg Emissionsmentioning
confidence: 99%
“…Life cycle studies have evaluated lignocellulosic ethanol production from a variety of feedstocks including: corn stover, switchgrass, hybrid poplar, alfalfa and reed canary grass (e.g., Sheehan et al 2004;Spatari et al 2005;Kim and Dale, 2005;Adler et al, 2007, GonzalezGarcia et al, 2010Wang et al 2012). The studies examined the production and use in road transportation vehicles of ethanol/gasoline blends in the forms of E10 (10 vol% ethanol), E85 (85 vol% ethanol), and E100 (100% ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…Recent analysis has shown that sufficient land exists in the U.S. Corn Belt to support a cellulosic ethanol industry without impacting productive cropland [18,39,40]. The effect of dedicated energy crops and corn grain on indirect land use change varies significantly based on the assumptions and models used [13,41,42] but bioenergy crops grown on marginally-productive cropland will have less impact on indirect land use change than bioenergy crops grown on more productive cropland. Likewise, model assumptions underlying direct SOC sequestration will impact system evaluations of GHG emissions and mitigation.…”
Section: Resultsmentioning
confidence: 99%
“…Biofuels from cellulosic feedstocks (e.g. corn stover, dedicated perennial energy grasses) are expected to have lower GHG emissions than conventional gasoline or corn grain ethanol [9][10][11][12][13]. Furthermore, dedicated perennial bioenergy crop systems such as switchgrass (Panicum virgatum L.) have the ability to significantly increase SOC [14][15][16] while providing substantial biomass quantities for conversion into biofuels under proper management [17,18].…”
Section: Introductionmentioning
confidence: 99%